Work-Related Musculoskeletal Disorders among Practicing Plastic Surgeons in India: A Cross-Sectional Survey - Aditya B. Marathe; Piyush V. Bamnodkar; Ankur S. Karanjkar; Parag B. Sahasrabudhe; Nikhil S. Panse (Indian Journal of Plastic Surgery)
Introduction Work-related musculoskeletal disorders (WRMDs) are a less discussed entity in the medical profession, with surgical specialties being more prone to them. Little is known about these types of injuries in plastic surgeons specifically. Data on WRMDs among Indian plastic surgeons are lacking. The goals of this study were to evaluate the prevalence, nature, particular contributory causal factors and behaviors, and potential remedies of these musculoskeletal injuries among plastic surgeons in India.